La Cour Africaine des Droits de l’Homme : la liberté de circulation des étrangers et l’intégration africaine. Observations rétrospectives sur l’arrêt Ikili Rashidi contre République-Unie de Tanzanie du 28 mars 2019 - Moyen, Léandre SergeI (Revue Africaine des Sciences Juridiques, Administratives et Politiques, 2024)
La Cour africaine était sollicitée pour répondre à la question de savoir si les ressortissants des États africains peuvent avoir droit, au même titre que les nationaux d’un État, à une égale protection en ce qui concerne la liberté de circulation et de séjour, c’est-à-dire de choisir librement leur résidence sur le territoire d’un État membre de l’Union africaine et signataire de la Charte africaine des droits de l’homme, même quand la régularité de leur séjour n’est pas formellement établie. Cette question fait directement référence à la problématique de l’intégration africaine, et en s’inscrivant dans la perspective intégrationniste, il était possible d’y répondre par l’affirmative. Au regard de l’idéal politique panafricain de l’unité politique affirmé pas le traité constitutif de l’Union africaine, la Cour pouvait interpréter la Charte africaine des droits de l’homme ou la Déclaration universelle des droits de l’homme comme autorisant les ressortissants des États africains à établir leur résidence où ils le souhaitent sur n’importe quel territoire d’un État membre de l’Union. Mais l’absence d’une citoyenneté africaine a conduit la Cour à lire l’article 3 de la Charte africaine dans le sens opposé. Ce faisant, elle entérine le renforcement des législations nationales, qui se sont inspirées des législations européennes très restrictives à l’égard de l’entrée et du séjour des étrangers sur le territoire de l’Union européenne. Elle s’est abstenue de créer du droit substantiel, alors qu’elle avait toute latitude pour le faire, à l’instar de la Cour européenne qui limite volontiers le pouvoir souverain des États en matière de protection des droits fondamentaux des personnes. Cette attitude prudente s’est confirmée dans l’appréciation des règles du procès équitable, où la Cour fait un usage modéré des pouvoirs que lui confèrent les articles 56 alinéas 5 et 6 de la Charte africaine et 40 § 6 du Règlement de la Cour, bien que le cadre conventionnel soit plastique. En définitive, la Cour africaine n’a pas été conçue pour accompagner l’unité politique africaine ; elle n’est pas l’instrument de mise en œuvre de la politique d’intégration africaine, et la décision Ikili Rashidi montre à coup sûr les limites de l’office du juge panafricain dans la protection des droits et libertés des citoyens. Il est impératif que les États s’orientent vers l’institution du contrôle de constitutionnalité des lois à l’échelle fédérale, ce qui semble être la seule alternative permettant la mise en place d’une justice réellement souveraine au service de l’intégration.
Keywords: Cour africaine des droits de l’homme; Dignité humaine; Droits fondamentaux de la personne; Etranger; Expulsion; Intérêt supérieur de l’enfant; Justice (administration); Liberté de circulation; Procès équitable; Vie familiale; Vie privée

The Challenges of Adoption of Eco Single Currency among ECOWAS Member-States - Anele, Livinus; Anuga, Joseph (African Journal of Politics and Administrative Studies, 2024)
The Economic Community of West African States, ECOWAS, had an agreement to adopt the Eco as its single currency for the fifteen member-states of the West African Sub-regional organization. This major objective has failed to materialize after a long period of time. This paper, therefore seeks to highlight the major challenges confronting the Eco currency project. Data were collected from secondary sources, using content analysis. The paper of discusses the challenges facing the proposed Eco single currency in West Africa, discusses the theoretical framework of monetary integration using Mundell’s factors of Mobility Theory and Mundell’s Optimum Currency Area Theory applied. Based on the findings, Some of the challenges facing the proposed Eco currency in ECOWAS include lack of political will, influence of France on its former territories in West Africa, membership of multiple regional blocs by member states of ECOWAS and fear of domination of the smaller states in the bigger ones. Other challenges include; security and political challenges, inadequate legal instruments to enforce treaty obligations, inadequate modern infrastructure among others. To make this proposed Eco currency a success, the paper suggests that West Africa Monetary Zone member states must take concrete action by showing political will towards the creation of Eco currency area in West Africa. There should be clearly spelt out benefits and costs accruing to each member state in the proposed Eco community currency area. All member states of ECOWAS must be treated as equal partners.
Keywords: Adoption; Anglophone-Francophone; Development; ECOWAS; Eco single currency

From red tape to red carpet: the Unidroit Cape Town Convention and MAC Protocol’s Adventure in Africa - Otabor-Olubor, Iyare (Uniform Law Review, 2024)
This article examines the implementation of the Mining, Agricultural and Construction (MAC) Equipment Protocol under the Cape Town Convention in Africa, focusing on enhancing economic growth and sustainable development through improved access to financing for high-value mobile equipment. Africa’s economic development is significantly hindered by inadequate infrastructure, which escalates transaction costs and limits access to international markets. Investment in modern infrastructure, particularly in the mining, agricultural, and construction sectors, is typically expensive for many businesses in the African region. The MAC Protocol aims to address these challenges by providing a uniform legal framework that supports the financing of MAC equipment. The Convention and the MAC Protocol facilitate access to affordable capital and reduce risks for financiers who take international interests in MAC equipment, promoting economic activities in Africa. The article highlights the legal protections offered by the MAC Protocol, ensuring rights against third-party claims and enhancing the enforceability of international interests. The adoption of the MAC Protocol by African States could significantly impact their ability to meet the United Nations Sustainable Development Goals by making modern, cost-efficient equipment more accessible, thus boosting productivity and economic diversification. The article advocates for adopting the MAC Protocol, emphasizing its potential to enhance foreign investment in the mining, agriculture, and construction sectors, stimulating economic development in Africa. This strategic move will propel African countries towards greater economic resilience and integration into the global economy. The article also critically analyses and illustrates the several declaration mechanisms available to countries adopting the MAC Protocol, accompanied by a guidance note to sensitize lawmakers when signing and/or ratifying or acceding to the Cape Town Convention and the MAC Protocol.

La libre circulation des personnes dans l'espace CEDEAO-UEMOA - Zouho, Bagnon César (Université de Strasbourg, 2024)
Intervenant sur le même espace régional, les deux principales organisations de l’Afrique de l’ouest à savoir la Communauté Economique Des Etats d’Afrique de l’Ouest (CEDEAO) et l’Union Economique et Monétaire Ouest Africaine (UEMOA) partagent l’objectif de parvenir à la libre circulation des personnes. Pourtant, il est constamment relevé que les droits qui devraient faciliter cette mobilité sont loin d’être mis en œuvre et qu’un contraste subsiste entre l’objectif de parvenir à la réalisation effective du principe de la libre circulation des personnes et les pratiques qui traduisent un exercice limite de cette liberté. La présente étude a trait aux problématiques en lien avec la question migratoire en Afrique de l’ouest, rend compte de l’adéquation apparente du régime adopte par la CEDEAO et l’UEMOA a l’effet de doter le principe de la libre circulation des personnes d’une véritable assise juridique. Il apparait ainsi que la qualité de cet ensemble de normes découle aussi bien de la diversification des bénéficiaires que de la cohérence de son contenu. Toutefois, l’analyse des modalités de réalisation du régime mis en place révèle des imperfections tenant aussi bien à la construction incomplète, qu’à l’application ineffective du droit de la libre circulation des personnes dans l’espace CEDEAO -UEMOA. Au demeurant la présence de facteurs extra-juridiques découlant des divergences et incohérences observées dans les positions des acteurs notamment les Etats, les organisations régionales et les peuples ouest-africains, laisse entrevoir la persistance d’obstacles d’ordre pratique qui compromettent l’atteinte des objectifs. Il s’ensuit que la libre circulation des personnes dans l’espace CEDEAO -UEMOA doit être considéré comme un processus dynamique dont l’évolution dépend de la capacite de l’ensemble des acteurs à réinventer des réponses adaptées a la spécificité des problématiques et contexte ouest-africains.
Keywords: Afrique occidentale; Borders; CEDEAO; Communauté économique des États de l'Afrique de l'Ouest; ECOWAS; Etats; Free movement of people; Frontières; Intégration régionale; Libre circulation des personnes; Regional integration; States; Travailleur; UEMOA; Union économique et monétaire Ouest africaine; Visa; Worker

The efficient enforcement challenge of secured transactions law reforms in civil law systems: self-help repossession, strict foreclosure, and other methods for the acceleration of enforcement of security interests - Tajti (Thaythy), Tibor (Uniform Law Review, 2024)
Although the forging of an efficient system for enforcement of security interest is one of the central expectations of secured transaction law reforms in civil law systems, the results hardly give reason for satisfaction. As the reforms tend to be supported and influenced by various international organizations’ projects (especially the World Bank, the European Bank for Reconstruction and Development, the International Institute for the Unification of Private Law, and the United Nations Commission on International Trade Law), most out-of-court methods of enforcement of security interests have played a central role. Yet due to civil law’s general hostility towards self-help as such, either the introduction of the concept has been rejected or the local limited-reach kin have been merely ‘paper tigers’. Similarly, although security interests on several types of collateral (accounts, investment property) or on the workhorse of the English financial system—the floating charge—have also been enforced extrajudicially (save the exceptions), little attention has been attributed to these enforcement modalities. The same applies to strict foreclosure in civil law systems still being prohibited, or restricted, and thus rarely resorted to, due to the inherited hostility towards the doctrine of lex commissoria. Rethinking local laws on preliminary and temporary court orders to match them with such globally known ex parte preliminary measures as the English Mareva Injunction or the French Saisie Conservatoire, which allow creditors to swiftly freeze debtors’ assets and thus substitute self-help repossession, has also been given short shrift. The enforcement segment, consequently, remains the Achilles’ heel of secured transaction law reforms in civil law systems. This article desires to contribute to reform literature by addressing these deficiencies and by offering tested, fully or partially fitting, functional equivalents of self-help repossession.

States and Regional International Organizations - Zouapet, Apollin Koagne (International Organizations Law Review, 2024)
Beyond the thorny, even insoluble question of the definition of a region and the definition of the criteria that should make it possible to apprehend the polymorphism of rio s, the raison d’être of these organizations, their mode of operation and their activities are at the heart of the debate on “international governance”. For many authors, the advent of RIO s has often been seen as a challenge to the state monopoly in the international legal order and a redefinition of the relationship between these particular organizations and states. It is this relational dynamic between the States and the RIO s that this contribution aims to describe and analyse. The aim is to examine the originality and specificity of the relationship between the RIO s and the States, compared to the latter’s relationship with the ‘classic/universal’ ios, which would reveal something about the very nature of regional organizations.
PDF: https://brill.com/downloadpdf/view/journals/iolr/21/1/article-p147_008.pdf
Keywords: Cooperation; Instrumentalism; Integration; Regionalism; Supranationalism; Universalism

The Impact of the United Nations Human Rights Treaties on the Domestic Level: Twenty Years On - Heyns, Christof; Viljoen, Frans Jacobus; Murray, Rachel (Brill, 2024)
This collection of chapters tracks and explains the impact of the nine core United Nations human rights treaties in 20 selected countries, four from each of the five UN regions. Researchers based in each of these countries were responsible for the chapters, in which they assess the influence of the treaties and treaty body recommendations on legislation, policies, court decisions and practices. By covering the 20 years between July 1999 and June 2019, this book updates a study done 20 years ago.
PDF: https://brill.com/downloadpdf/edcollbook-oa/title/38945.pdf
Keywords: Comparative Social Sciences; Human Rights; Human Rights and Humanitarian Law; Humanitarian Law; International Law; International Law: Regional Perspectives

The Impact of the United Nations Human Rights Treaties on the Domestic Level in Senegal - Kane, Ibrahima (The Impact of the United Nations Human Rights Treaties on the Domestic Level: Twenty Years On, 2024)
"Chapter 16 The Impact of the United Nations Human Rights Treaties on the Domestic Level in Senegal" published on 09 Feb 2024 by Brill | Nijhoff.
Section: The Impact of the United Nations Human Rights Treaties on the Domestic Level: Twenty Years On
Keywords: Comparative Social Sciences; Human Rights; Human Rights and Humanitarian Law; Humanitarian Law; International Law; International Law: Regional Perspectives; Social Sciences

Uniform Law: Legal Responses to Globalisation - Basedow, Jürgen; Max-Planck-Institut für Ausländisches und Internationales Privatrecht (Hamburg, Germany) (Mohr Siebeck, 2024)
International conference proceedings
Keywords: COMMERCIAL LAW; Economic Analysis; PRIVATE INTERNATIONAL LAW; Uniform law

L’OHADA et les ressources naturelles - Dieudonné, Barnabas (Revue Africaine des Réflexions Juridiques et Politiques, 2024)
Les ressources naturelles occupent une place prépondérante dans le commerce international. L’Afrique en est riche. Par contre, le problème de leur gestion se fait sentir sur le continent au point que des chercheurs ont évoqué la « malédiction des ressources naturelles ». Le droit de l’OHADA ne les a pris en compte que timidement. Cette insuffisance de règlementation dans le droit communautaire a des incidences tant sur le commerce de ces produits dans l’espace OHADA que sur la jouissance de certains droits humains. Les tentatives de règlementation de certains aspects de ce secteur d’activité de la part d’autres organisations internationales et de certains États montrent la nécessité de les intégrer correctement dans le corpus juridique de l’OHADA. Un Acte Uniforme serait susceptible d’atténuer, au sein des États parties, la « malédiction des ressources naturelles » aussi bien que les atteintes aux droits de la personne résultant de leur exploitation comme le droit à un environnement sain et les droits économiques et sociaux.
Keywords: Acte uniforme; Droits humains; Ressources naturelles; Règlementation

Les mesures provisoires devant la Commission et la Cour africaines des droits de l'homme et des peuples - Fall, Marie (Université de Genève, 2024)
La protection provisoire devant la Commission et la Cour africaines des droits de l’homme et des peuples est l’un des domaines du système africain de protection des droits et des peuples jusque-là loin d’être défriché de manière exhaustive. Pourtant, la mise en œuvre du dispositif des mesures provisoires dans le contexte africain remonte à l’établissement de la Commission africaine. Cette thèse propose de scruter le régime juridique exact des mesures provisoires et les contours de la pratique. La thèse ici défendue est que malgré les difficultés que peut poser le régime des mesures provisoires, la Commission et la Cour africaines en font un mécanisme au service de la protection effective des droits fondamentaux des requérants. Toutefois, la concrétisation de cette finalité est compromise par le taux élevé d’inexécution de ces mesures en raison des insuffisances dont souffre la procédure devant ces organes auxquelles s’ajoute la mauvaise volonté des États parties. Cette thèse formule ainsi des solutions qui permettent à la Cour et à la Commission d’exploiter le potentiel du régime des mesures provisoires comme instrument au service de la garantie effective des droits fondamentaux des individus protégés par la CADHP.
Keywords: CADHP; Intégration régionale

Measuring the Effects of Post-Convention Activities at the HCCH - Zhang, Ke (McGill University, 2024)
https://escholarship.mcgill.ca/concern/theses/cn69m944k
Keywords: HCCH; Hague Conference on Private International Law